2011
DOI: 10.3390/s110302700
|View full text |Cite
|
Sign up to set email alerts
|

A Nanosensor for TNT Detection Based on Molecularly Imprinted Polymers and Surface Enhanced Raman Scattering

Abstract: We report on a new sensor strategy that integrates molecularly imprinted polymers (MIPs) with surface enhanced Raman scattering (SERS). The sensor was developed to detect the explosive, 2,4,6-trinitrotoluene (TNT). Micron thick films of sol gel-derived xerogels were deposited on a SERS-active surface as the sensing layer. Xerogels were molecularly imprinted for TNT using non-covalent interactions with the polymer matrix. Binding of the TNT within the polymer matrix results in unique SERS bands, which allow for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
133
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 32 publications
0
133
0
1
Order By: Relevance
“…3 Various analytical and spectroscopic methods have been developed for sensitive detection of NA compounds. [4][5][6][7] These instrumental techniques are mostly expensive and not portable for use in the field. The detection of NA explosives using fluorescent-based sensors has been extensively studied because of their sensitivity, portability, and short response time.…”
mentioning
confidence: 99%
“…3 Various analytical and spectroscopic methods have been developed for sensitive detection of NA compounds. [4][5][6][7] These instrumental techniques are mostly expensive and not portable for use in the field. The detection of NA explosives using fluorescent-based sensors has been extensively studied because of their sensitivity, portability, and short response time.…”
mentioning
confidence: 99%
“…There is, however, a significant disadvantage of antibodies when it comes to direct detection of the analyte because their relatively large size sets a large distance between the analyte and the substrate. There are other capturing molecules that are gaining some attention such as enzymes, molecularly imprinted polymers, and affimers [151][152][153]. While they hold promise for functional SERS assays, they have yet to gain momentum for both research and real-world applications.…”
Section: Functional Assaysmentioning
confidence: 99%
“…The integrated MIP for explosives detection has shown that it is selective to 2,4-DNT and has demonstrated reliable reversibility and stability. 18 In this work, the gas sensing experiment was performed with the noise-squeezing controller at a concentration of 0.93 parts-per-billion (ppb) 2,4-DNT. Figure 5 presents the change in the natural frequency of the microbeam sensor over time as it is challenged with 2,4-DNT.…”
Section: Mip Integration and Sensor Performancementioning
confidence: 99%
“…16,17 In this work, molecularly imprinted xerogel thin films have demonstrated selectivity and stability in combination with a fixed-fixed beam MEMS cantilever. 18,19 Traditionally, mass sensing using MEMS resonators has been achieved based on the natural frequency shift due to an increase in resonator mass; however, noise has set the limit of detection for linear sensing. 20 As an alternative to using changes in the natural frequency, nonlinear dynamics induced by parametric excitation have led to successful cantilever-based sensor designs.…”
Section: Introductionmentioning
confidence: 99%